Different Nutritional Systems at Suckling and Finishing Phases of Lambs Grazing on Tropical Pasture - J. A. da Silva; C. C. B. F. Ítavo; L. C. V. Ítavo; F. A. Batista; M. M. S. Peres; N. S. Heimbach; G. K. A. de Melo; P. C. G. da Silva; K. L. S. M. Ferelli; T. F. F. S. Arco; C. de Godoy; A. A. S. Miguel (Tropical Animal Science Journal, 2022)
The objective of the study was to evaluate the lambs' performance in the suckling and finishing phases in different nutritional systems. The study was carried out in two phases: suckling (from birth to weaning) and finishing (from weaning to slaughter). Each phase was evaluated in two experimental periods (characterized by year). The suckling phase used 76 lambs divided into two groups: control (without supplementation) and creep feeding (with creep feeder supplementation of 20 g/kg of body weight). The lambs were distributed in the treatments according to sex and type of delivery (single or twin). The finishing phase was characterized from weaning to slaughter. Sixty-two lambs were used, 28 females and 34 males, average age of 85 days and an average weight of 19 kg, and the animals were distributed in treatments according to weight and sex. Five treatments were evaluated, animals in Brachiaria spp. receiving increasing levels of supplementation (0%, 0.8%, 1.6%, and 2.4% of BW) and confinement as a positive performance control. The creep feeding treatment presented superior performance with an average daily gain of 64.85 g more than the control treatment, which anticipated the shorter age at weaning with higher weaning weight (weaning in 64 days for supplemented lambs and 77 days for animals without supplementation). In the finishing phases, the lambs of the treatments 1.6%BW and 2.4%BW presented average daily gain similar to the confined animals and higher (p<0.05) than the treatments 0.8%BW and 0%BW. We recommend that ad libitum supplementation of creep feeding during the suckling phase is a nutritional strategy to wean heavier lambs and consequently reduce time in the finishing phase. For fattening the lambs, we recommend the inclusion of protein-energy supplementation of 1.6% BW for lambs produced in the tropical pasture.